Proteomics revisits the cancer metabolome. (August 2011) - Hu, Hao; Deng, Cao; Yang, Tao; Dong, Qiang; Chen, Ya; Nice, Edouard C; Huang, Canhua; Wei, Yuquan
Many cancer cells utilize aerobic glycolysis (also known as the 'Warburg effect''), instead of mitochondrial oxidative phosphorylation, to generate the energy necessary for diverse cellular processes. In tumor cells, mitochondria play more important roles in anabolism, for instance, de novo lipid biosynthesis and glutamine-dependent anaplerosis to fuel robust cell growth and proliferation. Proteomic analysis of tumor-related alterations of metabolism-associated proteins clearly indicates that such metabolic reprogramming contributes to cancer cell survival and cancer progression. Moreover, proteomics-based systems biology provides a powerful tool to re-evaluate the metabolic phenotype and regulatory mechanism associated with malignant cancer cells, and underscores their implications for cancer diagnosis and therapy. This article will address recent exciting advances in the understanding of cancer cell metabolism using proteomics-based systems biology approaches.